An immigrant soldier in the Mexican War - Zeh, Frederick, 1823-1902? (Elma Dill Russell Spencer series in the West and Southwest ;, 1995)
"Frederick Zeh, a young German immigrant, had hardly arrived in the United States when he was caught up in the war fever that swept his new homeland. He joined the Mountain Howitzer and Rocket Company of the U.S. Army. His impressions of the siege of Veracruz, the long march to Mexico City, the bloody battles that occurred along the route, and the occupation of the capital provide a vivid and unusual account of the Mexican War from an enlisted man's point of view." "Although Zeh held the lowly rank of "laborer" in the army, he was well-educated and an astute observer, and his story is both lively and well-written. Besides the horror of battles, he tells about relations between officers and enlisted men, military punishment, and the day-to-day life of the soldiers. Numerous anecdotes and personal stories enliven his narrative. He is unusually candid about abuses that occurred in the American army and toward Mexican civilians. His is also the first book-length account written by a German-American participant - a significant contribution, given that nearly half the regular army was made up of immigrant recruits."--Jacket